The effects of crime on Irish victims : psychological and organisational perspectives - Cooper, Joanne (Trinity College (Dublin, Ireland). School of Psychology, 2003)
"The Effects of Crime on Irish Victims: Psychological and Organisational Perspectives" is, as its name suggests, an investigation of the impact of criminal victimisation in Ireland from both a psychological and a victim support perspective. It originated as a request from Victim Support. Ireland to have its services evaluated. As the evaluation was being planned, however, it became apparent that a dearth of knowledge existed on crime victimisation and its effects in an Irish context. This led to the dual focus of the thesis. It was discovered, however, that each perspective served to enrich the other, the support organisation benefiting from learning more about the psychological experiences of its service user group and the possibility of the psychological effects of crime being lessened by the support organisation improving the quality of its service to crime victims.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin